INVESTIGATION OF ROCKING CURVE OF REFLECTION ON SINGLE CRYSTALS OF ADP UNDER INFLUENCE OF TEMPERATURE GRADIENT - M. Ghannad Dezfouli; Trouni, K. G.; V. R. Kocharyan
Rocking curves of reflectivity for ADP crystal have been measured under influence of temperature gradient in Laue-case geometry. We observed that increase in value of the temperature gradient lead to increase of reflectivity and also increase of width of rocking curve slightly. Experimental results are compared with theoretical results based on the asymptotic solution of dynamical diffraction of X-ray wave in crystals with weak deformation. An agreement between both results is obtained.
Keywords: Physics; Acoustics; Materials science